Spectrophotometric method for hg(ii) determination in aqueous environment using zinc-dithizonate complex - Musa Ahmad Ahmad; Elya Sufliza Marsom; Harun Hamzah (ASEAN Journal on Science and Technology for Development, 2001)
This article described the use of zinc-dithizonate for spectrophotometric  determination of Hg(II) in aqueous environment. Zinc dithizonate was found to react selectively with Hg(II) to give a reddish yellow complex  with  optimum  absorbance  at  pH  1.0. This complex was found to be useful for  spectrophotometric determination of aqueous Hg(II) in the concentration range of 1.0 - 12.0 ppm. This method was also found to be reproducible with calculated relative standard deviation, RSD of 1.08%. At 1:1 mole ratio, interfering ions such as CH COO·, Pb2+ and Ag+ were found to interfere at degree 3 of interference of more than 10.0%.